Unia Europejska i jej otoczenie - zasięg przestrzenny oraz kierunki specjalnej współpracy - Cybulski, Leszek (European Union and its surroundings - spatial range and directions of spatial co-operation, 2006)
The enlargement of the EU with Turkey is very popular in mass media and covers all other problems connected with expanding of the EU including the region of West Balkans. In the next ten years the, number of member countries will probably exceed 30. Usually no one remembers that the UE could change its range without changing the number of its members. The case of including German Landers could be repeated by Northern Cyprus. Among priorities of the European Foreign and Security Policy could be found strengthening of the European political and economic stability by for example co-operation with neighbour countries and developing ones - former colonies. This paper brings nearer these less known forms of co-operation (countries and territories ENP, AKP, OCT). It is difficult to expect to raise these issues on the level of full integration in the medium-term but in further future it cannot be excluded because right now EU lies on 5 continents.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 122-133